A novel ion-pairing chromatographic method for the simultaneous determination of both nicarbazin components in feed additives: Chemometric tools for improving the optimization and validation - de Zan, María Mercedes (2011)
The development, optimization and validation of an ion-pairing high performance liquid chromatography method for the simultaneous determination of both nicarbazin (NIC) components: 4,4-dinitrocarbanilide (DNC) and 2-hydroxy-4,6-dimethylpyrimidine (HDP) in bulk materials and feed additives are described. An experimental design was used for the optimization of the chromatographic system. Four variables, including mobile phase composition and oven temperature, were analyzed through a central composite design exploring their contribution to analyte separation. Five responses: peak resolutions, HDP capacity factor, HDP tailing and analysis time, were modelled by using the response surface methodology and were optimized simultaneously by implementing the desirability function. The optimum conditions resulted in a mobile phase consisting of 10.0mmolL−1 of 1-heptanesulfonate, 20.0mmolL−1 of sodium acetate, pH= 3.30 buffer and acetonitrile in a gradient system at a flow rate of 1.00mLmin−1. Column was an INERSTIL ODS-3 (4.6mm×150mm, 5mparticle size) at 40.0 ◦C. Detection was performed at 300nm by a diode array detector. The validation results of the method indicated a high selectivity and good precision characteristics, with RSD less than 1.0% for both components, both in intra and inter-assay precision studies. Linearity was proved for a range of 32.0?50.0gmL−1 of NIC in sample solution. The recovery, studied at three different fortification levels, varied from 98.0 to 101.4 for HDP and from 99.1 to 100.2 for DNC. The applicability of the method was demonstrated by determining DNC and HDP content in raw materials and commercial formulations used for coccidiosis prevention. Assays results on real samples showed that considerable differences in molecular ratio DNC:HDP exist among them.